Wiel Arets (A+U)
Se compilas obras y artículos teóricos del arquitecto. Contiene: A Virological Architecture por Wiel Arets. Maastricht Academy for the Arts and Architecture, 1990-1993. Groningen Court Building, 1991. Delft Theater, 1992. Rotterdam, Two Residential Tower Blocks, 1992-1993. An Alabaster Skin por Wiel Arets. Amsterdam Academy for the Arts, 1990. Domburg Boulevard, 1990. Amsterdam, Residential Towe Block, 1990-1993. Maastricht Commercial Office, 1993. Maastricht Fashion Shop, 1986-1987. Hapert Medical Center and House, 1988-1989.